El turismo cultural en Granada: una oportunidad de diversidad turística (Altre Modernità, 2012)
The article entitled "Cultural Tourism in Granada: Diversity of Tourism Opportunity", shows theoretical various definitions of cultural tourism, as well as characteristics and relation with urban tourism and city. The theoretical framework guides the research carried out in Granada through a survey. Presents the main results found in the research and the Tourism Action Plan for the city of Granada for properly manage, and solve the problems that have become apparent in research.